Formaldehyde catalytic conversion and decomposition method
Through graphite-like carbon nitride/metal phase materials embedded with zinc, copper and manganese, the catalytic conversion of formaldehyde is accelerated by using the redox reaction base group to accelerate the catalytic conversion of formaldehyde, the problems of low formaldehyde purification efficiency and high energy consumption in the existing technology are solved, and high efficiency is achieved The catalytic conversion of formaldehyde significantly improves the purification effect and efficiency.
Patent Information
- Application Number
- CN202411525895.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
AI Technical Summary
The existing formaldehyde purification methods have the problem of formaldehyde re-release when temperature and humidity fluctuate, and the purification rate is low and energy consumption is high, making it difficult to meet the long-term high-efficiency indoor air purification needs in crowded places.
Using graphite-like carbon nitride/metallic phase materials embedded with zinc, copper and manganese, formaldehyde is converted into water and carbon dioxide through oxygen adsorption and catalytic reaction, and catalytic is accelerated by Zn-Cu and Mn-Zn redox reaction base groups. The conversion process improves the catalytic conversion rate and rate.
The efficient catalytic conversion of formaldehyde has been achieved, with the catalytic conversion rate increased from 80% to 95%, and the catalytic conversion rate increased from 8ppm/h to 14ppm/h, reducing the harm of formaldehyde to the human body and the environment and reducing the purification cost.
Smart Images

Figure CN119186252A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waste gas treatment, and in particular to a formaldehyde catalytic conversion and decomposition method. Background Art
[0002] Formaldehyde, also known as formic aldehyde, is an organic compound, a colorless gas. It is not easy to detect at low concentrations and can be easily masked by other odors, such as air fresheners. At high concentrations, it has a strong irritating and suffocating odor, which is irritating to the eyes and nose. Formaldehyde is a toxic gas that seriously endangers human health. It is more common in furniture and decoration materials that do not meet quality standards. If patients are in an environment with high formaldehyde concentrations for a long time, they may experience dizziness, headaches, tears, nausea and vomiting, coughing, chest tightness, leukemia, etc., and severe cases may lead to death. Therefore, we should pay attention to staying away from formaldehyde in our lives, ventilate newly renovated houses frequently, and pay attention to monitoring the formaldehyde content.
[0003] Formaldehyde is one of the main indoor gaseous pollutants that are harmful to human health. It has the characteristics of long active period, wide sources and coexistence with various pollutants. Therefore, it is urgent to purify it efficiently. The existing formaldehyde purification methods are mainly based on adsorption capture and ventilation. For example, CN200810036746.2 once disclosed a formaldehyde adsorbent containing chitosan; CN117654442A once disclosed a modified porous adsorption material for removing formaldehyde and its preparation method. In this existing method, the adsorption capture method will cause formaldehyde to be released again when the temperature and humidity fluctuate, and the ventilation method will cause atmospheric pollution around the building, that is, both methods are difficult to completely purify formaldehyde. In addition, the purification rate of the above-mentioned adsorption purification method is low, and the average energy consumption of the ventilation method is high, which cannot meet the needs of long-term and efficient indoor air purification in crowded places such as classrooms and libraries.
[0004] Therefore, how to provide a formaldehyde catalytic conversion and decomposition method that can more efficiently achieve formaldehyde treatment in indoor air has become a problem that needs to be considered and solved by those skilled in the art. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the technical problem to be solved by the present invention is: how to provide a formaldehyde catalytic conversion and decomposition method that can more efficiently achieve formaldehyde treatment in indoor air, so as to reduce the harm of formaldehyde to the human body and the home environment.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A formaldehyde catalytic conversion and decomposition method, characterized in that it comprises the following steps: In the first step, oxygen is adsorbed on the surface of graphite-like carbon nitride / metal phase material and decomposed into two oxygen atoms; the reaction formula can be represented as O2(free) + g-C3N4 / Zn / Cu / Mn → O2(ad), O2(ad) → * O a + * O b ; In the second step, formaldehyde is adsorbed on the surface of the graphite-like carbon nitride / metal phase and reacts with (part of) the oxygen atoms generated in the first step to form formic acid; the reaction formula can be represented as HCHO + g-C3N4 / Zn / Cu / Mn → HCHO(ad), HCHO(ad)+ * O a → * HCOO a H(ad); In the third step, the formic acid molecule loses two hydrogen atoms to form carbon dioxide. The two hydrogen atoms combine with the (other) oxygen atoms generated in the first step to form water molecules. * HCOO a H(ad) → OC- * O a + * H a + * H b , * H a + * H b + * O b →H a -O b -H b .
[0007] In this way, the present invention uses a graphite-like carbon nitride / metal phase material embedded with zinc, copper and manganese as a catalytic conversion treatment material for formaldehyde, and can quickly and efficiently achieve catalytic conversion adsorption treatment of formaldehyde through the above reaction treatment process. In this process, firstly, the graphite-like carbon nitride can provide abundant adsorption sites for a large number of formaldehyde and oxygen molecules to adsorb, greatly improving the catalytic reaction rate; secondly, the embedded Zn, Cu and Mn metal atoms can respectively form two groups of redox reaction groups, which are used to strengthen the above formaldehyde catalytic conversion process.
[0008] Furthermore, in the present invention, a graphite-like carbon nitride / metal phase formaldehyde catalytic conversion and decomposition treatment material whose main effective components are zinc, copper and manganese as metal phases is used to achieve catalytic conversion treatment of formaldehyde.
[0009] In the above-mentioned formaldehyde catalytic conversion and decomposition treatment materials, the specific working principles and processes of the three types of metal phases are as follows.
[0010] (a) The Zn-Cu redox reaction group is used in the above process of formaldehyde reacting with free oxygen atoms to produce formic acid, which mainly includes two steps: the carbon atom of formaldehyde combines with the free oxygen atom to form a bond (H2OC + * O → H2OC··· * O), a hydrogen atom of formaldehyde combines with the free oxygen atom to form a bond (H2OC··· * O → O=HC- * OH). Zn atoms can lose their outer valence electrons to free oxygen atoms, converting them into oxygen atom free radicals -• O, while the hydrogen atoms of formaldehyde easily lose electrons to Cu atoms to form free hydrogen atom free radicals +• H, oxygen atom free radicals bond with the carbon atom of formaldehyde, and the free hydrogen atom free radicals further bond with the bonded oxygen atom free radicals to finally form adsorbed formic acid molecules. In the above process, Zn atoms are reducing agents and Cu atoms are oxidizing agents, which enhance the breaking and formation of chemical bonds by losing and gaining electrons, respectively, thereby accelerating the conversion process of "formaldehyde → formic acid".
[0011] (b) The Mn-Zn redox reaction group is used in the process of removing two hydrogen atoms from the formic acid molecule to form carbon dioxide and water molecules. It can be divided into two steps: the breaking of the carbon-hydrogen bond / oxygen-hydrogen bond in the formic acid molecule and the combination of the free hydrogen atom and the free oxygen atom. According to different chemical environments, a single Mn atom can provide 2, 4, 6 or 7 outer valence electrons to the hydrogen atoms in the formic acid molecule, converting them into quasi-free radical forms, increasing their energy to break away from the carbon-hydrogen bond / oxygen-hydrogen bond (i.e., chemical bond breaking), and forming adsorbed carbon dioxide and free hydrogen atom free radicals. In the process of further combining with free oxygen atoms to form water molecules, the free hydrogen atom free radical will lose excess free radical electrons to Zn atoms. In the above process, Mn is a reducing agent and Zn is an oxidizing agent. They enhance the breaking and formation of chemical bonds by losing and gaining valence electrons, respectively, and realize the "formic acid → carbon dioxide + water" conversion process.
[0012] (c) In the above processes (a) and (b), Zn acts as a reducing agent and an oxidizing agent, respectively, thereby realizing the recycling of Zn metal atoms. It should be noted that since the metal activity of Zn is stronger than that of Cu, in the process (b), Mn-Cu can also form a redox reaction group, further accelerating the above formaldehyde catalytic conversion process.
[0013] Therefore, the present invention can simultaneously improve the catalytic conversion rate and catalytic conversion rate of formaldehyde. The applicant has verified that the present invention can increase the catalytic conversion rate of formaldehyde from ~80% increased to 95%+; the formaldehyde catalytic conversion rate increased from 8ppm / h to ~ 14ppm / h.
[0014] Furthermore, the formaldehyde catalytic conversion and decomposition treatment material adopted in the present invention includes the following phase components in the following mass proportions: 0.01-0.15 parts of pure graphite-like carbon nitride phase, 0.01-0.05 parts of metal oxide phase (ZnO, CuO and MnO2), 0.01-0.12 parts of metal phase (Zn, Cu and Mn), 0.05-0.10 parts of graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2), and 0.58-0.92 parts of graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn).
[0015] Further better mass proportions are: 0.02 parts of pure graphite-like carbon nitride phase, 0.01 parts of metal oxide phase (ZnO, CuO and MnO2), 0.10 parts of metal phase (Zn, Cu and Mn), 0.02 parts of graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2), and 0.85 parts of graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn).
[0016] In the above-mentioned formaldehyde catalytic conversion and decomposition treatment materials, graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn) is the main effective ingredient and accounts for a large proportion, which is the main place for formaldehyde catalytic conversion; at the same time, other phase components, as common reaction products, can play a certain dynamic conversion supplement effect after the main effective ingredients are converted and consumed (especially the presence of metal phases Zn, Cu and Mn), thereby better ensuring the durability of the treatment effect.
[0017] Furthermore, the formaldehyde catalytic conversion and decomposition treatment material is prepared by the following steps: Step 1: Weigh 1.5 mol of melamine and pour it into 500 ml of 95% or more pure alcohol, stir, dissolve and evaporate to obtain loose agglomerates, grind them into powder and place them in an aluminum crucible, calcine them to generate graphite-like carbon nitride (the preferred calcination reaction process is to heat from room temperature to 600 ° C at a rate of 30 ° C / min and continue calcining for 2.5 h in an air atmosphere, and then naturally ventilate and cool to room temperature to obtain a light yellow block object), grind them into 300 mesh powder; Step 2: Pour the above 300-mesh powder into 1 L of deionized water and evenly disperse it (preferably using an ultrasonic cleaner for dispersion, with an ultrasonic treatment time of 1 h) to form a stable yellow suspension; Step 3: Pour 0.5 mol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.5 mol of copper nitrate hexahydrate (Cu(NO3)2·2.5H2O) and 0.5 mol of manganese nitrate hexahydrate (Mn(NO3)2·6H2O) into the yellow suspension, stir and mix evenly to obtain a light yellow / light blue / light rose red block (preferably, stir and mix continuously at 50°C and 200 r / min for 3 h in a magnetic stirrer, then evaporate and consume all water at 50°C in a drying oven to obtain a light yellow / light blue / light rose red block), and further grind it into 300 mesh powder; Step 4: Place the above-mentioned light yellow / light blue / light rose red 300 mesh powder in an aluminum crucible, and calcine the reaction (preferably heating from room temperature to 800 °C at a rate of 30 °C / min and continuing the calcination reaction for 2.5 h in a hydrogen (H2) atmosphere), and then naturally ventilate and cool to room temperature to obtain the final desired powdered formaldehyde catalytic conversion and decomposition treatment material.
[0018] The number of each raw material product in the above steps can be adjusted in equal proportion. The chemical reaction process of each step in the preparation process of the catalytic conversion treatment material includes: In step 1, melamine reacts with oxygen to form graphite-like carbon nitride, and the reaction equation is: C3H6N6 + O2→ C3N4 + H2O; In step 4, zinc nitrate, copper nitrate and manganese nitrate attached to the surface of the graphite-like carbon nitride are decomposed to generate corresponding metal oxides, which are further reduced by hydrogen to generate corresponding metal single atoms and embedded in the graphite-like carbon nitride.
[0019] The decomposition reactions of zinc nitrate, copper nitrate and manganese nitrate are Zn(NO3)2 → ZnO + NO2 + O2, Cu(NO3)2 → CuO + NO2 + O2 and Mn(NO3)2 → MnO2 + NO2 + O2, respectively.
[0020] The reactions for the reduction of ZnO, CuO and MnO2 by hydrogen are ZnO + H2 → Zn + H2O, CuO + H2 → Cu+ H2O and MnO2 + H2 → Mn + H2O, respectively.
[0021] The reaction in which Zn, Cu and Mn are embedded in the graphite-like carbon nitride and replace part of the nitrogen atoms is Zn + Cu + Mn +C3N4 →··· C···Zn···C···Cu···N···Mn···C···.
[0022] Therefore, the above reaction process can quickly and efficiently produce a formaldehyde catalytic conversion and decomposition treatment material with the main effective components of graphite phase carbon nitride / metal phase (metal is Zn, Cu and Mn) accounting for more than 50%, ensuring the efficient catalytic conversion reaction treatment effect after the adsorption of formaldehyde. At the same time, other phase components generated are evenly mixed and doped together, especially the presence of some metal phases Zn, Cu and Mn, which can play a certain dynamic conversion supplement effect after the main effective components are converted and consumed, and better ensure the durability of the catalytic treatment effect on formaldehyde.
[0023] Therefore, the present invention has the following characteristics: 1. Formaldehyde is catalytically converted into water and carbon dioxide, which in principle reduces the harm of formaldehyde to the human body and the environment; 2. The efficiency of formaldehyde catalytic conversion is improved to achieve long-term purification of indoor formaldehyde; 3. The cost of the formaldehyde catalytic conversion operation process is reduced to increase the universal scope of formaldehyde catalytic conversion purification technology.
[0024] In summary, the present invention can more efficiently implement the formaldehyde catalytic conversion and decomposition method for treating formaldehyde in indoor air, thereby reducing the harm of formaldehyde to the human body and the home environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the principle process of catalytic conversion of formaldehyde by the formaldehyde catalytic conversion and decomposition treatment material of the present invention.
[0026] Figure 2 It is a schematic diagram comparing the formaldehyde catalytic conversion rate of the formaldehyde catalytic conversion and decomposition treatment material of the present invention and other types of formaldehyde catalyst materials.
[0027] Figure 3 It is a schematic diagram comparing the formaldehyde catalytic conversion rate of the formaldehyde catalytic conversion decomposition treatment material of the present invention and other types of formaldehyde catalyst materials. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with specific implementation modes.
[0029] Implementation method: A formaldehyde catalytic conversion and decomposition method, which is characterized by comprising the following steps: In the first step, oxygen is adsorbed on the surface of graphite-like carbon nitride / metal phase material and decomposed into two oxygen atoms; the reaction formula can be represented as O2(free) + g-C3N4 / Zn / Cu / Mn → O2(ad), O2(ad) → * O a + * O b ; In the second step, formaldehyde is adsorbed on the surface of the graphite-like carbon nitride / metal phase and reacts with (part of) the oxygen atoms generated in the first step to form formic acid; the reaction formula can be represented as HCHO + g-C3N4 / Zn / Cu / Mn → HCHO(ad), HCHO(ad)+ * O a → * HCOO a H(ad); In the third step, the formic acid molecule loses two hydrogen atoms to form carbon dioxide. The two hydrogen atoms combine with the (other) oxygen atoms generated in the first step to form water molecules. * HCOO a H(ad) → OC- * O a + * H a + * H b , * H a + * H b + * O b →H a -O b -H b .
[0030] In this way, the present invention uses a graphite-like carbon nitride / metal phase material embedded with zinc, copper and manganese as a catalytic conversion treatment material for formaldehyde, and can quickly and efficiently achieve catalytic conversion adsorption treatment of formaldehyde through the above reaction treatment process. In this process, firstly, the graphite-like carbon nitride can provide abundant adsorption sites for a large number of formaldehyde and oxygen molecules to adsorb, greatly improving the catalytic reaction rate; secondly, the embedded Zn, Cu and Mn metal atoms can respectively form two groups of redox reaction groups, which are used to strengthen the above formaldehyde catalytic conversion process.
[0031] Specifically, in the above method, a graphite-like carbon nitride / metal phase formaldehyde catalytic conversion and decomposition treatment material whose main effective components are zinc, copper and manganese as metal phases is used to achieve catalytic conversion treatment of formaldehyde.
[0032] In the above-mentioned formaldehyde catalytic conversion and decomposition treatment materials, the specific working principle of the three types of metal phases is as follows, see Figure 1 The basic reaction process is: the formaldehyde and oxygen molecules in the upper left corner are catalyzed by the Zn / Cu / Mn atoms supported on the graphite-like carbon nitride surface to form carbon dioxide and water molecules in the lower right corner. The bold red arrow indicates the direction of the reaction surface.
[0033] (a) The Zn-Cu redox reaction group is used in the above process of formaldehyde reacting with free oxygen atoms to produce formic acid, which mainly includes two steps: the carbon atom of formaldehyde combines with the free oxygen atom to form a bond (H2OC + * O → H2OC··· * O), a hydrogen atom of formaldehyde combines with the free oxygen atom to form a bond (H2OC··· * O → O=HC- * OH). Zn atoms can lose their outer valence electrons to free oxygen atoms, converting them into oxygen atom free radicals -• O, while the hydrogen atoms of formaldehyde easily lose electrons to Cu atoms to form free hydrogen atom free radicals +• H, oxygen atom free radicals bond with the carbon atom of formaldehyde, and the free hydrogen atom free radicals further bond with the bonded oxygen atom free radicals to finally form adsorbed formic acid molecules. In the above process, Zn atoms are reducing agents and Cu atoms are oxidizing agents, which enhance the breaking and formation of chemical bonds by losing and gaining electrons, respectively, thereby accelerating the conversion process of "formaldehyde → formic acid".
[0034] (b) The Mn-Zn redox reaction group is used in the process of removing two hydrogen atoms from the formic acid molecule to form carbon dioxide and water molecules. It can be divided into two steps: the breaking of the carbon-hydrogen bond / oxygen-hydrogen bond in the formic acid molecule and the combination of the free hydrogen atom and the free oxygen atom. According to different chemical environments, a single Mn atom can provide 2, 4, 6 or 7 outer valence electrons to the hydrogen atoms in the formic acid molecule, converting them into quasi-free radical forms, increasing their energy to break away from the carbon-hydrogen bond / oxygen-hydrogen bond (i.e., chemical bond breaking), and forming adsorbed carbon dioxide and free hydrogen atom free radicals. In the process of further combining with free oxygen atoms to form water molecules, the free hydrogen atom free radical will lose excess free radical electrons to Zn atoms. In the above process, Mn is a reducing agent and Zn is an oxidizing agent. They enhance the breaking and formation of chemical bonds by losing and gaining valence electrons, respectively, and realize the "formic acid → carbon dioxide + water" conversion process.
[0035] (c) In the above processes (a) and (b), Zn acts as a reducing agent and an oxidizing agent, respectively, thereby realizing the recycling of Zn metal atoms. It should be noted that since the metal activity of Zn is stronger than that of Cu, in the process (b), Mn-Cu can also form a redox reaction group, further accelerating the above formaldehyde catalytic conversion process.
[0036] Therefore, the present invention can simultaneously improve the catalytic conversion rate and catalytic conversion rate of formaldehyde. The applicant has verified that the present invention can increase the catalytic conversion rate of formaldehyde from ~ 80% increased to 95%+; the formaldehyde catalytic conversion rate increased from 8ppm / h to ~ 14ppm / h.
[0037] The above-mentioned formaldehyde catalytic conversion and decomposition treatment material includes the following phase components in the following mass proportions: 0.01-0.15 parts of pure graphite-like carbon nitride phase, 0.01-0.05 parts of metal oxide phase (ZnO, CuO and MnO2), 0.01-0.12 parts of metal phase (Zn, Cu and Mn), 0.05-0.10 parts of graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2), and 0.58-0.92 parts of graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn).
[0038] Further better mass proportions are: 0.02 parts of pure graphite-like carbon nitride phase, 0.01 parts of metal oxide phase (ZnO, CuO and MnO2), 0.10 parts of metal phase (Zn, Cu and Mn), 0.02 parts of graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2), and 0.85 parts of graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn).
[0039] In the above-mentioned formaldehyde catalytic conversion and decomposition treatment materials, graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn) is the main effective ingredient and accounts for a large proportion, which is the main place for formaldehyde catalytic conversion; at the same time, other phase components, as common reaction products, can play a certain dynamic conversion supplement effect after the main effective ingredients are converted and consumed (especially the presence of metal phases Zn, Cu and Mn), thereby better ensuring the durability of the treatment effect.
[0040] In specific implementation, the formaldehyde catalytic conversion and decomposition treatment material is prepared by the following steps: Step 1: Weigh 1.5 mol of melamine (C3H6N6, high-grade purity 99.9%) and pour it into 500 ml of 95% or more pure alcohol for stirring, dissolving and evaporation to obtain loose agglomerates, grind them into powder and place them in an aluminum crucible, heat them from room temperature to 600 °C at a rate of 30 °C / min and continue calcining for 2.5 h in an air atmosphere, then naturally ventilate and cool them to room temperature to obtain a light yellow block object, which is ground into 300 mesh powder; Step 2: Pour the above 300-mesh powder into 1 L of deionized water, and use an ultrasonic cleaner to evenly disperse it. The ultrasonic treatment time is 1 h to form a stable yellow suspension; Step 3: Pour 0.5 mol of zinc nitrate hexahydrate (Zn(NO3)2·6H2O), 0.5 mol of copper nitrate hexahydrate (Cu(NO3)2·2.5H2O) and 0.5 mol of manganese nitrate hexahydrate (Mn(NO3)2·6H2O) into the yellow suspension, stir and mix in a magnetic stirrer at 50°C and 200 r / min for 3 h, then evaporate all the water in a drying oven at 50°C to obtain a light yellow / light blue / light rose red block, which is further ground into 300 mesh powder; Step 4: Place the above-mentioned light yellow / light blue / light rose red 300 mesh powder in an aluminum crucible, heat it from room temperature to 800 °C at a rate of 30 °C / min, and continue calcining reaction for 2.5 h in a hydrogen (H2) atmosphere, then naturally ventilate and cool to room temperature to obtain the final powdered formaldehyde catalytic conversion and decomposition treatment material.
[0041] The number of each raw material product in the above steps can be adjusted in equal proportion. The chemical reaction process of each step in the preparation process of the catalytic conversion treatment material includes: In step 1, melamine reacts with oxygen to form graphite-like carbon nitride, and the reaction equation is: C3H6N6 + O2→ C3N4 + H2O; In step 4, zinc nitrate, copper nitrate and manganese nitrate attached to the surface of the graphite-like carbon nitride are decomposed to generate corresponding metal oxides, which are further reduced by hydrogen to generate corresponding metal single atoms and embedded in the graphite-like carbon nitride.
[0042] The decomposition reactions of zinc nitrate, copper nitrate and manganese nitrate are Zn(NO3)2 → ZnO + NO2 + O2, Cu(NO3)2 → CuO + NO2 + O2 and Mn(NO3)2 → MnO2 + NO2 + O2, respectively.
[0043] The reactions for the reduction of ZnO, CuO and MnO2 by hydrogen are ZnO + H2 → Zn + H2O, CuO + H2 → Cu+ H2O and MnO2 + H2 → Mn + H2O, respectively.
[0044] The reaction in which Zn, Cu and Mn are embedded in the graphite-like carbon nitride and replace part of the nitrogen atoms is Zn + Cu + Mn +C3N4 →··· C···Zn···C···Cu···N···Mn···C···.
[0045] Therefore, the above reaction process can quickly and efficiently produce a formaldehyde catalytic conversion and decomposition treatment material with the main effective components of graphite phase carbon nitride / metal phase (metal is Zn, Cu and Mn) accounting for more than 50%, ensuring the efficient catalytic conversion reaction treatment effect after the adsorption of formaldehyde. At the same time, other phase components generated are evenly mixed and doped together, especially the presence of some metal phases Zn, Cu and Mn, which can play a certain dynamic conversion supplement effect after the main effective components are converted and consumed, and better ensure the durability of the catalytic treatment effect on formaldehyde.
[0046] In order to better verify the effect of the present invention, the applicant conducted a comparative experiment, using the formaldehyde catalytic conversion and decomposition treatment material obtained in the above specific implementation method as the experimental group, and using pure graphite-like carbon nitride, graphite-like carbon nitride loaded with Zn, graphite-like carbon nitride loaded with Cu and graphite-like carbon nitride loaded with Mn as the control group under the environmental conditions of 80°C / 1 bar / 50% relative humidity, respectively, to conduct a 50 ppm formaldehyde catalytic conversion efficiency comparison experiment. Figure 2 From the experimental results, it can be seen that the formaldehyde catalytic conversion rate of pure graphite-like carbon nitride or graphite-like carbon nitride loaded with a single type of metal is lower than that of graphite-like carbon nitride loaded with three metals at the same time. In particular, the formaldehyde catalytic conversion rate of graphite-like carbon nitride loaded with three metals at the same time is much higher than that of pure graphite-like carbon nitride and graphite-like carbon nitride loaded with Zn, indicating that the simultaneous loading of three metals can make the graphite-like carbon nitride catalytic conversion of formaldehyde produce a synergistic effect and greatly enhance the catalytic conversion ability of graphite-like carbon nitride.
[0047] for Figure 3 In the environmental conditions of 80 ℃ / 1 bar / 50% relative humidity, a 50 ppm formaldehyde catalytic conversion rate comparison experiment was carried out with pure graphite-like carbon nitride, graphite-like carbon nitride loaded with Zn, graphite-like carbon nitride loaded with Cu and graphite-like carbon nitride loaded with Mn as control groups. Figure 3 It is a schematic diagram of the comparative test results. From the experimental results, it can be seen that the formaldehyde catalytic conversion rate of pure graphite-like carbon nitride or graphite-like carbon nitride loaded with a single type of metal is lower than that of graphite-like carbon nitride loaded with three metals at the same time, especially the formaldehyde catalytic conversion rate of graphite-like carbon nitride loaded with three metals at the same time is much higher than that of pure graphite-like carbon nitride and graphite-like carbon nitride loaded with Zn, indicating that the simultaneous loading of three metals can make the graphite-like carbon nitride catalytic conversion of formaldehyde have a synergistic effect and greatly enhance the catalytic conversion ability of graphite-like carbon nitride.
Claims
1. A method for catalytic conversion and decomposition of formaldehyde, characterized in that: The following steps are involved: In the first step, oxygen is adsorbed on the surface of the graphite-like carbon nitride / metal phase material and decomposed into two oxygen atoms; In the second step, formaldehyde is adsorbed on the surface of the graphite-like carbon nitride / metal phase and reacts with (a portion of) the oxygen atoms generated in the first step to form formic acid; In the third step, the formic acid molecule loses two hydrogen atoms to form carbon dioxide, and the two hydrogen atoms combine with the (other part of) oxygen atoms generated in the first step to form a water molecule.
2. The formaldehyde catalytic conversion and decomposition method according to claim 1, characterized in that: The method adopts a graphite-like carbon nitride / metal phase formaldehyde catalytic conversion and decomposition treatment material whose main effective components are zinc, copper and manganese as metal phases to achieve catalytic conversion treatment of formaldehyde.
3. The formaldehyde catalytic conversion and decomposition method according to claim 2, characterized in that: The formaldehyde catalytic conversion and decomposition treatment material includes the following phase components in the following mass proportions: 0.01-0.15 parts of pure graphite-like carbon nitride phase, 0.01-0.05 parts of metal oxide phase (ZnO, CuO and MnO2), 0.01-0.12 parts of metal phase (Zn, Cu and Mn), 0.05-0.10 parts of graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2), and 0.58-0.92 parts of graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn).
4. The formaldehyde catalytic conversion and decomposition method according to claim 3, characterized in that: Pure graphite-like carbon nitride phase 0.02 parts, metal oxide phase (ZnO, CuO and MnO2) 0.01 parts, metal phase (Zn, Cu and Mn) 0.10 parts, graphite-like carbon nitride / metal oxide phase (metal oxides are ZnO, CuO and MnO2) 0.02 parts, graphite-like carbon nitride / metal phase (metals are Zn, Cu and Mn) 0.85 parts.
5. The formaldehyde catalytic conversion and decomposition method according to claim 2, characterized in that: The formaldehyde catalytic conversion and decomposition treatment material is prepared by the following steps: Step 1: Weigh 1.5 mol of melamine and pour it into 500 ml of 95% or more pure alcohol, stir, dissolve and evaporate to obtain loose agglomerates, grind them into powder and place them in an aluminum crucible, calcine them to generate graphite-like carbon nitride, and grind them into 300 mesh powder; Step 2: Pour the above 300-mesh powder into 1 L of deionized water and evenly disperse it to form a stable yellow suspension; Step 3: Pour 0.5 mol of zinc nitrate hexahydrate, 0.5 mol of copper nitrate hexahydrate and 0.5 mol of manganese nitrate hexahydrate into the yellow suspension, stir and mix evenly to obtain a light yellow / light blue / light rose red block, which is further ground into 300 mesh powder; Step 4: Place the above-mentioned light yellow / light blue / light rose red 300 mesh powder in an aluminum crucible, calcine and react, and then naturally ventilate to cool to room temperature to obtain the final desired powdered formaldehyde catalytic conversion and decomposition treatment material.
6. The formaldehyde catalytic conversion and decomposition method according to claim 5, characterized in that: In step 1, the calcination reaction process is to increase the temperature from room temperature to 600 °C at a rate of 30 °C / min and continue calcining for 2.5 h in an air atmosphere, and then naturally ventilate to room temperature to obtain a light yellow block object.
7. The formaldehyde catalytic conversion and decomposition method according to claim 5, characterized in that: In step 2, an ultrasonic cleaning machine is used for dispersion, and the ultrasonic treatment time is 1 h.
8. The formaldehyde catalytic conversion and decomposition method according to claim 5, characterized in that: In step 3, stirring is performed in a magnetic stirrer at 50°C and 200 r / min for 3 h, and then all water is evaporated in a drying oven at 50°C to obtain a light yellow / light blue / light rose red block object.
9. The formaldehyde catalytic conversion and decomposition method according to claim 5, characterized in that: In step 4, the calcination temperature is increased from room temperature to 800 °C at a rate of 30 °C / min and the calcination reaction is continued for 2.5 h in a hydrogen atmosphere.
